How ready are we to move species threatened from climate change? Insights into the assisted colonization debate from Australia. (16th May 2014) - Hancock, Nola; Gallagher, Rachael
Abstract Assisted colonization, the intentional movement of species beyond their native range, has been proposed as a climate change adaptation tool for biodiversity conservation. The risks and benefits of its implementation are still being debated but already the climate is changing, species are moving and the pressure on at‐risk species must therefore be increasing. However, instances where moving species beyond their natural range purely for conservation purposes due to climate change are few, and the opportunity for science to inform practice is limited. Here we survey active participants in flora translocations and/or flora conservation in Australia in order to investigate the gap between theoretical and conceptual ideas about assisted colonization and to gauge preparedness for its implementation. We found that actions that mitigate proximal threats are preferred over those that move species beyond their current range. A lack of knowledge of species biology and ecology is an impediment to the acceptance of assisted colonization. In addition, prohibitive costs and the potential increased risk of the spread of diseases, pests and/or pathogens are viewed as more important obstacles of successful assisted colonization than potential for invasion at the recipient site. Full approval from all stakeholders at the source and recipient sites was found to be the most important factor for the successful assisted colonization of flora.